The Impact of Human Capital Development on Economic Growth in Ethiopia: Evidence from ARDL Approach to Co-Integration - Gebrehiwot, Kidanemariam Gidey (American Journal of Trade and Policy, 2014)
The main objective of the study was to investigate the long run and short run impact of human capital on economic growth in Ethiopia (using real GDP per capita, as a proxy for economic growth) over the period 1974/75-2010/2011. The ARDL Approach to Co-integration and Error Correction Model are applied in order to investigate the long-run and short run impact of Human capital on Economic growth. The finding of the Bounds test shows that there is a stable long run relationship between real GDP per capita, education human capital, health human capital, labor force, gross capital formation, government expenditure and official development assistance. The estimated long run model revels that human capital in the form of health (proxied by the ratio of public expenditure on health to real GDP) is the main contributor to real GDP per capita rise followed by education human capital (proxied by secondary school enrolment). Such findings are consistent with the endogenous growth theories which argue that an improvement in human capital (skilled and healthy workers) improves productivity. In the short run, the coefficient of error correction term is -0.7366 suggesting about 73.66 percent annual adjustment towards long run equilibrium. This is another proof for the existence of a stable long run relationship among the variables. The estimated coefficients of the short-run model indicate that education is the main contributor to real GDP per capita change followed by gross capital formation (one period lagged value) and government expenditure (one period lagged value). But, unlike its long run significant impact, health has no significant short run impact on the economy. Even its one period lag has a significant negative impact on the economy. The above results have an important policy implication. The findings of this paper imply that economic performance can be improved significantly when the ratio of public expenditure on health services to GDP increases and when secondary school enrolment improves. Such improvements have a large impact on human productivity which leads to improved national output per capita. Hence policy makers and / or the government should strive to create institutional capacity that increase school enrolment and improved basic health service by strengthening the infrastructure of educational and health institutions that produce quality manpower. In addition to its effort, the government should continue its leadership role in creating enabling environment that encourage better investment in human capital (education and health) by the private sector.